Cardiomyocyte specific peroxisome proliferator-activated receptor-α overexpression leads to irreversible damage in ischemic murine heart - Duerr, Georg D.; Heinemann, Jan C.; Arnoldi, Vanessa; Feisst, Andreas; Kley, Julian; Ghanem, Alexander; Welz, Armin; Dewald, Oliver (Life Sciences, 2014)
Aims Peroxisome proliferator-activated receptor (PPAR)-α is downregulated in ischemic myocardium resulting in substrate switch from fatty acid oxidation to glucose utilization. Pharmacological PPAR-α activation leads to increased fatty acid oxidation and myocardial lipotoxicity. The aim of our study was to investigate the role of cardiomyocyte specific PPAR-α overexpression in myocardial adaptation to repetitive ischemic injury without myocardial infarction. Main methods Repetitive, brief I/R was performed in male and female MHC-PPAR-α overexpressing and wildtype-C57/Bl6 (WT)-mice, age 10-12 weeks, for 3 and 7 consecutive days. After echocardiography, their hearts were excised for histology and gene/protein-expression measurements (Taqman/Western blot). Key findings MHC-PPAR-α mice developed microinfarctions already after 3 days of repetitive I/R in contrast to interstitial fibrosis in WT-mice. We found higher deposition of glycogen, increased apoptosis and dysfunctional regulation of antioxidative mediators in MHC-PPAR-α mice. MHC-PPAR-α mice presented with maladaptation of myosin heavy chain isoforms and worse left ventricular dysfunction than WT-mice. We found prolonged, chemokine-driven macrophage infiltration without induction of proinflammatory cytokines in MHC-PPAR-α mice. Persistent accumulation of myofibroblasts in microinfarctions indicated active remodeling resulting in scar formation in contrast to interstitial fibrosis without microinfarctions in WT-mice. However, MHC-PPAR-α hearts had only a weak induction of tenascin-C in contrast to its strong expression in WT-hearts. Significance Cardiomyocyte-specific PPAR-α overexpression led to irreversible cardiomyocyte loss with deteriorated ventricular function during brief, repetitive I/R episodes. We identified higher glycogen deposition, increased apoptosis, deranged antioxidative capacity and maladaptation of contractile elements as major contributors involved in the modulation of post-ischemic inflammation and remodeling. © 2014 Elsevier Inc.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Apoptosis; Chemokines; Diabetes; Inflammation; Ischemia/reperfusion; PPAR-α; Remodeling